2013
DOI: 10.1111/chd.12154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Sports Enjoyment and Leisure-time Spending in Adolescents with Complex Congenital Heart Disease: The Moderating Effect of Health Behavior and Disease Knowledge

Abstract: Exercise training decreased passive, but not active, leisure-time spending. It did not influence sports enjoyment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…This is not surprising as in adolescence contact with peers becomes increasingly important for social and emotional wellbeing, decisions about a (future) education and/or job have to be made, and exposure to all kinds of experimental behaviourfor example, smoking, alcohol, drugs, sex, etc.increases. 21 As to the different cardiac diagnostic groups, no significant differences were found with regard to their need for psychosocial care. This is in line with previous findings, reflecting no consistent relationship between cardiac diagnosis and emotional/behavioural problems in children with CHD.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is not surprising as in adolescence contact with peers becomes increasingly important for social and emotional wellbeing, decisions about a (future) education and/or job have to be made, and exposure to all kinds of experimental behaviourfor example, smoking, alcohol, drugs, sex, etc.increases. 21 As to the different cardiac diagnostic groups, no significant differences were found with regard to their need for psychosocial care. This is in line with previous findings, reflecting no consistent relationship between cardiac diagnosis and emotional/behavioural problems in children with CHD.…”
Section: Discussionmentioning
confidence: 87%
“…An expert psychologist (EU) selected the items based on international literature 2,26 and on previous cohort studies by and clinical experience of the research team. 11,21,[27][28][29][30] Consensus regarding items was reached between two psychologists, two paediatric cardiologists, and thereafter piloted by two board members of the Dutch patient organisation. After piloting and feedback, items were adjusted and finalised for the present questionnaire.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Groningen Enjoyment Questionnaire (GEQ; 10 items; response categories 1–3, higher score indicates more enjoyment) [ 37 , 38 ] is adjusted for parents and teachers and assesses enjoyment of physical activity. Children themselves answer two questions to assess how often they engage in physical activity and to assess enjoyment of physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…In this last study, the exercise program had an effect on self-reported passive leisure time spent [ 19 ]. After the program, adolescents spent less time on using the computer.…”
Section: The Influence Of An Exercise Program On Psychosocial Funcmentioning
confidence: 99%